Comparison of energy expenditure in adolescents when playing new generation and sedentary computer games: cross sectional study. Issue 7633 (20th December 2007) - Graves, Lee; Stratton, Gareth; Ridgers, N D; Cable, N T
Abstract : Objective To compare the energy expenditure of adolescents when playing sedentary and new generation active computer games. Design Cross sectional comparison of four computer games. Setting Research laboratories. Participants Six boys and five girls aged 13-15 years. Procedure Participants were fitted with a monitoring device validated to predict energy expenditure. They played four computer games for 15 minutes each. One of the games was sedentary (XBOX 360) and the other three were active (Wii Sports). Main outcome measure Predicted energy expenditure, compared using repeated measures analysis of variance. Results Mean (standard deviation) predicted energy expenditure when playing Wii Sports bowling (190.6 (22.2) kJ/kg/min), tennis (202.5 (31.5) kJ/kg/min), and boxing (198.1 (33.9) kJ/kg/min) was significantly greater than when playing sedentary games (125.5 (13.7) kJ/kg/min) (P<0.001). Predicted energy expenditure was at least 65.1 (95% confidence interval 47.3 to 82.9) kJ/kg/min greater when playing active rather than sedentary games. Conclusions Playing new generation active computer games uses significantly more energy than playing sedentary computer games but not as much energy as playing the sport itself. The energy used when playing active Wii Sports games was not of high enough intensity to contribute towards the recommended daily amount of exercise in children.